2020
DOI: 10.1590/1806-9061-2019-1180
|View full text |Cite
|
Sign up to set email alerts
|

Effects of β-mannanase on Egg Production Performance, Egg Quality, Intestinal Microbiota, Viscosity, and Ammonia Concentration in Laying Hens

Abstract: Two experiments were conducted to evaluate the effects of β-mannanase on egg production performance, egg quality, intestinal microbiota, viscosity, and ammonia concentration in laying hens. In Exp. 1, two hundred and seventy 30-wk-old Hy-Line Brown laying hens were assigned to 6 diets arranged in a 3 × 2 factorial of three levels of MEn and CP [(a corn-soybean meal based diet (HEHP), a diet containing 50 kcal of MEn/kg and 1.0% less energy and CP than the HEHP (MEMP), and a diet containing 80 kcal of MEn/kg an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…Based on our in vitro data in this paper, and published in vivo data (Kong et al, 2011;Mussini et al, 2011, Zheng et al, 2020 we can confirm the two modes of action of CTCzyme as an NSPase: (1) Solubilization of mannan in the cells walls to loosen and destroy the compact cell wall architecture thereby making the protein more bioavailable, and (2) Release of mannose oligomers considered to have prebiotic functions for improving gut health and integrity.…”
Section: Oligomsupporting
confidence: 67%
See 1 more Smart Citation
“…Based on our in vitro data in this paper, and published in vivo data (Kong et al, 2011;Mussini et al, 2011, Zheng et al, 2020 we can confirm the two modes of action of CTCzyme as an NSPase: (1) Solubilization of mannan in the cells walls to loosen and destroy the compact cell wall architecture thereby making the protein more bioavailable, and (2) Release of mannose oligomers considered to have prebiotic functions for improving gut health and integrity.…”
Section: Oligomsupporting
confidence: 67%
“…In the same way, using suboptimal nutrient levels in a broiler trial Ferreira et al (2016) showed an improved AMEn of 1.5% with the inclusion of CTCzyme. With supplementation of CTCzyme β-mannanase in a low-energy and low-protein diet, laying hens were able to maintain similar production performance when compared to a high-energy and high-protein diet during early and late egg production (Zheng et al, 2020). There was no inclusion of any low molecular weight fermentable oligosaccharides in the above mentioned in vivo work besides the enzyme as opposed to the work of Cordero et al (2019) which included both enzyme and fermentable oligosaccharides (in the experiment: a xylanase and xylan oligosaccharides).…”
Section: Oligommentioning
confidence: 99%
“…However, hens receiving a low AME diet with 0.04% β-mannanase had thicker eggshells than hens fed other diets. Supplemental β-mannanase (800,000 U/kg) had no effects on egg quality measures (shell color, thickness, strength, yolk color, and Haugh unit) during early and late lay in Hy-line brown hens ( Zheng et al, 2020 ).…”
Section: Introductionmentioning
confidence: 97%
“…However, the hens fed β-mannanase had higher egg production, egg mass, and retained more gross energy and crude protein. Supplemental β-mannanase (800,000 U/kg) in lower AME and crude protein diets resulted in comparable egg production and egg mass to high AME and crude protein diets during early (30 weeks) and late (>62 weeks) laying cycle in Hy-Line brown laying hens ( Zheng et al, 2020 ). The effect of dietary β-mannans (1.05% vs. 2.33%) and supplemental β-mannanase (0%, 0.04%, and 0.08%) was investigated for 8 weeks in 52-wk-old Hy-line brown hens ( Ryu et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…in the ileum and cecum. The effect of exogenous enzyme such as β-mannanase and xylanase on intestinal microorganism have been observed in previous studies [36][37][38][39]. Roofchaei et al [40] detected that the dietary supplemental xylanase, β-glucanase, and phytase in combination had an inhibitory effect on the E. coli population in the ileum.…”
Section: Discussionmentioning
confidence: 82%